ASSESSMENT OF THE CREATIVE POTENTIAL OF MODERN YOUTH - Мороз, Людмила (SWorldJournal, 2021)
The creative potential of modern adolescents is assessed on the example of high school students on the basis of identifying and analyzing the constituent parameters of creative potential, which is considered as mental processes that go beyond standard pat